PENYELESAIAN SENGKETA KETENAGAKERJAAN DIINDUSTRI PERHOTELAN MELALUI ARBITRASE DAN MEDIASI - Ni Wayan Seniasih; Komang Edy Dharmasaputra; Kadek Mery Herawati (Nusantara Hasana Journal, 2025)
The forms and characteristics of labor disputes occurring in the hotel industry show unique dynamics, in line with the nature of the industry which is labor-intensive, service-based, and highly dependent on customer satisfaction. In general, the dominant forms of disputes include; 1) rights disputes, such as late salary payments, underpayment of overtime, wage deductions without legal basis and neglect of normative rights such as leave and social security, 2) interest disputes, such as disputes regarding the service charge distribution system, changes in working hour policies without workers' consent or demands for increased welfare, 3) layoff disputes, which often occur unilaterally by hotel management for reasons of efficiency or disciplinary violations that are not based on proper legal procedures. The characteristics of labor disputes in the hotel industry include; recurring and structural in nature, especially in terms of wages and working hours, involving unequal power relations between management and workers, which makes internal resolution difficult, often not well documented, because some workers are non-permanent or casual, have a direct impact on the reputation and sustainability of the hotel business, considering the nature of the industry that prioritizes image and service. Thus, it can be said that the resolution of labor disputes in the hotel industry requires a comprehensive approach, not only based on positive law but also considering the sociological conditions of the employment relationship, as well as supporting a resolution mechanism that is fast, fair and maintains the stability of industrial relations. The mechanism for resolving labor disputes through mediation and arbitration in the hotel industry has great potential in preventing the escalation of conflict that can be detrimental to both parties and damage the image of the hotel business. However, its effectiveness is highly dependent on an understanding of the law, a commitment to social dialogue, and the commitment of the parties to resolve the problem peacefully outside the litigation channel.